GREB1‐CTNNB1 fusion transcript detected by RNA‐sequencing in a uterine tumor resembling ovarian sex cord tumor (UTROSCT): A novel CTNNB1 rearrangement. Issue 3 (7th January 2019) - Croce, Sabrina; Lesluyes, Tom; Delespaul, Lucile; Bonhomme, Benjamin; Pérot, Gaëlle; Velasco, Valérie; Mayeur, Laetitia; Rebier, Flora; Ben Rejeb, Houda; Guyon, Frédéric; McCluggage, W Glenn; Floquet, Anne; et al.
Abstract : Mutations of CTNNB1 have been implicated in tumorigenesis in many organs. However, tumors harboring a CTNNB1 translocation are extremely rare and this translocation has never been reported in a uterine mesenchymal neoplasm. We report a novel translocation t(2;3)(p25;p22) involving the GREB1 (intron 8) and CTNNB1 (exon 3) in a uterine tumor resembling ovarian sex cord tumor (UTROSCT), which exhibited extrauterine metastasis. The translocation detected by RNA‐sequencing was validated by RT‐PCR, and resulted in nuclear expression of β‐catenin. Juxtapositioning with GREB1, which is overexpressed in response to estrogens, resulted in overexpression of a truncated and hypophosphorylated nuclear β‐catenin in the primary and recurrent tumors. This accumulation of nuclear β‐catenin results in a constitutive activation of the Wnt/β‐catenin signaling pathway with a major oncogenic effect. The CTNNB1 gene fusion, promoted by an estrogen‐responsive gene ( GREB1 ), could be a potential driver of tumorigenesis in this case and a therapeutic target with adapted inhibitors. RT‐PCR and immunohistochemistry performed on 11 additional UTROSCTs showed no CTNNB1 fusion transcript or nuclear β‐catenin immunoreactivity.